Current and future research on the association between gut microbiota and breast cancer - Liu, Kuan; Jia, Nan; Shi, Hongyun; Ran, Yuge (Frontiers in Microbiology, 2023)
Breast cancer (BC) is a prevalent malignancy. There exists a strong association between gut microbiota (GM) and the development of BC. The GM composition in individuals with BC significantly differs from that in their healthy counterparts. Furthermore, the distribution of GM varies significantly among individuals with different types of BC. The GM can impact BC through metabolite secretion, the gut-mammary axis, and other pathways. Modulating the GM can serve as a very promising potential therapeutic strategy in the treatment of BC. This article will summarize existing research, focusing on the relationship between intestinal microbiota and BC. At the same time, the project will also analyze the application value of intestinal microorganisms in BC intervention work, so as to provide a reference for the further development of BC prevention and treatment work.